2010
DOI: 10.1007/s00296-010-1652-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser in the treatment of carpal tunnel syndrome: clinical, electrophysiological, and ultrasonographical evaluation

Abstract: The objective of this study is to investigate the efficacy of low-level laser therapy (LLLT) in patients with carpal tunnel syndrome (CTS). Sixty patients with CTS were included in this placebo-controlled and double-blind study and randomly assigned to three treatment groups: active laser with a dosage of 1.2 J/per painful point, active laser with a dosage of 0.6 J/per painful point, and placebo groups. A total of 5 points across the median nerve trace were irradiated with Gal-Al-As diode laser. All groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…[ 23 , 24 ] The blindness of the participants and personnel was not clear in 2 studies, [ 23 , 32 ] and the blindness of the outcome assessment was not described in 4 studies. [ 23 , 24 , 31 , 32 ] The details of the methodological quality of the included studies are presented in Fig. 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 , 24 ] The blindness of the participants and personnel was not clear in 2 studies, [ 23 , 32 ] and the blindness of the outcome assessment was not described in 4 studies. [ 23 , 24 , 31 , 32 ] The details of the methodological quality of the included studies are presented in Fig. 2 .…”
Section: Resultsmentioning
confidence: 99%
“…One study found no statistically significant clinical differences between the group of patients treated with laser and the placebo group, but improved sensory conduction in patients who received Laser was observed, similarly to our data. 23 The Spearman correlation test between clinical data and conduction studies parameters showed no statistic significance. As the Spearman correlation test applies predominantly to ordinal scale variables, and, as in our study the only ordinal scale used was the VAS (visual analogue scale of pain, ranging from zero to ten), we opted for conducting also the Pearson correlation test.…”
Section: Discussionmentioning
confidence: 99%
“…LLL therapy (LLLT) was suggested as a simple and non-invasive option in the treatment of TTS. Mechanisms implicated in its action include enhancement of the local microcirculation, improvement of axonal myelination, and augmented release of endorphins 13 . Therefore, this study proposed to evaluate the effect of LLLT on clinical symptoms and neurophysiological parameters in type II diabetic patients with TTS.…”
Section: Introductionmentioning
confidence: 99%